"IN A PLACE PARALLEL TO GOD": THE DRAFT, THE DEMONIC, AND THE CONSCIENTIOUS CUBIST - Berman, Nathaniel (Journal of law and religion, 2017)
The question "What is religion?" has again been roiling the academy, the courts, and public debate. In 1965, the Supreme Court of the United States opined on this question, deciding the fate of would-be conscientious objectors who would not affirm the existence of God. Relying largely on Paul Tillich, the Court ruled in their favor, expanding the notion of "religious belief" beyond its conventional Western confines. This article reexamines the issues raised in this case by exploring the theology of Paul Tillich, particularly its critique of religion as a separate sphere and its challenge to basic tenets of liberal political theory inherited from John Locke. The article, however, also juxtaposes the religion-expanding aspects of Tillich's thought with his strictures about "demonic" distortions of religion, requiring an excursus into Tillich's notions of the divine/demonic relationship. Tillich's rejection of the compartmentalization of "religion" led him to declare that more religious meaning may be found in putatively "secular" artifacts, such as Cubist art, than in conventionally "religious" symbols and institutions, including the Church. This approach both demands a radically interdisciplinary approach to "religion" and casts a skeptical eye on some putatively "religious" claims. The article concludes by juxtaposing Tillich's anti-essentialist critique of "religion" with more recent, and dramatically different, critiques, particularly those advanced by Talal Asad and Saba Mahmood.